(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Social mobility refers to the movement of individuals or groups within or between social strata in a society. Education plays a pivotal role in enhancing social mobility by providing individuals with the skills, knowledge, and opportunities to improve their socio-economic status. This research paper examines the role of education in promoting social mobility in the Parbhani District of the Marathwada region, Maharashtra, India. Using dummy data, we analyze how access to education impacts income, employment, and social status. The findings suggest that education significantly improves social mobility, particularly in rural areas.